Konten Edukatif di Instagram: Studi Kasus Tasya Farasya Approved - Febriansis, Diva; Yulianti Fajar Wulandari; Ali Imron Hamid (Prisani Cendekia Institute, 2025)
Social media today serves not only as a means of communication and entertainment, but has also become a space for people to obtain information and knowledge. Instagram, as one of the most popular visual platforms, has given rise to the phenomenon of influencers who play a significant role in shaping public opinion. One prominent figure is Tasya Farasya, a beauty influencer known for her